Implementasi Konsep "Kuda Sandel" Pada Interior Bangunan Utama Arena Pacuan Kuda - Pasuruan - Crystaline Ongkowidjojo (Intra, 2014)
Nowadays, the sport of horseback riding in East Java is growing rapidly. It can be seen from the game of horse racing and equestrian/horseback riding stunt more often held, as well as the increasing number of population of horse breeder in East Java. The regional administrator of East Java’s PORDASI had the idea to build a horse racing and equestrian field complete with amenities. According to the survey results, in Indonesia, Pulomas Jakarta is the only horse racing field which has buildings and spaces inside. However, the building and the interior are not designed properly.The design aims to answer the needs at the racetrack for both athletes, Jockey, trainer, groom/nurse horses, horse owners, administrators, and fans of this sports.  From the concept, themed “The Sandalwood Horse”, the designer found 3 major keywords, those keywords are: horses, local, and blending. This design implements the horses’ characteristics, physical surroundings, and other objects that are associated with the horse into the interior design, then combined it with local natural material to create the impression of natural space. This design has answered all the problems of the space requirements as well as the circulation of the interior of the main building in the racetrack optimally, and also can give the horse atmosphere from the interior of the building, especially on the interior elements and furniture.